Analisis Naratif Dalam Film Uang Panai Ditinjau Dari Perspektif Komunikasi Islam - Ramli; Iskandar; Zainuddin, Zulkifli Zainuddin (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
Film is a communicative medium in conveying messages, because the message to be conveyed is visualized through visual scenes or film sound. The film Uang Panai is a regional film that raises the issue of the local wisdom of the Makassar Bugis tribe regarding marriage dowries in the romantic and religious comedy genre. This film tells about the phenomenon of the Makassar Bugis tradition which in general is the most important thing in a wedding ceremony, where a man who wants to get married must prepare Uang Panai as a condition for marriage. This research is a qualitative research that makes the film Uang Panai as the object of research and focuses on narrative analysis using observation and documentation data collection techniques. The data source for this research is the entire content of the film Uang Panai' by Halim Gani Safia which was released on August 25 2016 in all Indonesian cinemas with a duration of 119 minutes or 1 hour 59 minutes. The results of the study show that the various scenes and dialogues shown in the film Uang Panai show that the film represents the story of a couple who are about to get married, where the man must collect Uang Panai as a condition for marriage (spending money) to be given to the bride in accordance with the prevailing customs in society. Bugis-Makassar. As for Islamic values in the Uang Panai film where Anca is full of endeavor, exerts all her efforts in fighting for her love for Risna, stands firm and does not complain about all the trials and problems in collecting Uang Panai, and is responsible for all the decisions she makes, proves Taro There is Taro Gau (sticking to what is said). The application of the principles of Islamic communication in the film Uang Panai can be seen in that every problem that arises is resolved by good, gentle, effective and easy to understand communication.